1971
DOI: 10.1002/bjs.1800581010
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and pathogenesis of tracheal injury following tracheostomy with cuffed tube and assisted ventilation analysis of a 3-year prospective study

Abstract: Observations are reported from a 3‐year prospective study of tracheal injury occurring in patients managed by cuffed‐tube tracheostomy and assisted ventilation in the Respiratory Failure Unit at Toronto General Hospital. When the cuffed tracheostomy tube was finally removed an initial bronchoscopic examination of the trachea was performed. Further clinical and radiological assessments were made 3 weeks and 3 months later, using bronchoscopy when indicated. The incidence of symptomatic tracheal stenosis in 153 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Tables Z and ZI summarize some pertinent data relating to the 59 tracheal strictures. T h e prospective study mentioned previously (Andrews, 1971;Andrews and Pearson, 1971) indicated the following conclusions :-I. Tracheostomy tubes of large diameter were associated with an increased incidence of strictures at the level of the original tracheostome.…”
Section: Methodsmentioning
confidence: 89%
See 3 more Smart Citations
“…Tables Z and ZI summarize some pertinent data relating to the 59 tracheal strictures. T h e prospective study mentioned previously (Andrews, 1971;Andrews and Pearson, 1971) indicated the following conclusions :-I. Tracheostomy tubes of large diameter were associated with an increased incidence of strictures at the level of the original tracheostome.…”
Section: Methodsmentioning
confidence: 89%
“…Thirty-two of the strictures were seen during a 3-year period of a prospective study which was designed to determine the true incidence of this complication, and to clarify the pathogenesis of tracheal injury in those patients requiring tracheostomy and assisted ventilation. T h e results of this prospective study have been previously reported (Andrews, 1971;Andrews and Pearson, 1971)-…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Despite improvements in respiratory care, including widespread use of low‐pressure, high‐volume cuffed tubes, tracheal stenosis remains a feared complication of prolonged endotracheal intubation and tracheostomy. The reported incidence of tracheal stenosis following tracheostomy ranges from 0.6 to 21% 21,22 and following laryngotracheal intubation ranges from 6 to 21% 23 . In a prospective study, complications of tracheostomy have been reported to be more common and more severe compared to endotracheal intubation 24 .…”
Section: Discussionmentioning
confidence: 99%